Gatunki filozoficzne - Gabriel Lîiceanu (Przestrzenie Teorii)
The article is devoted to various philosophical genres, such as the treatise, essay, fragment, tale, letter, and dialogue. These are not treated as comfrotable and transparent means by which to express philosophical thought: on the contrary, they are closely related to the form through which such thoughts are expressed. The author does not limit himself to describing these written forms of philosophy, but confronts two fundamental types of thought, which are expressed in two distinct types of writing. One of these is “priestly”: authoritative, systemic, based on monologue, on a single, self-confident subject, while the other is “ecumenical” thought: based no dialogue, rooted in the here and now, closer to the fragment. The former type is artificial thought, aware of the temptations of totalitarianism or “thought imperialism”; the latter, on the other hand, is based on a living and natural train of thought. Systemic thought finds expression in a writing style whose aim is clear from the outset, where the act of writing is merely a conduit for absolute meanings; by contrast, dialogue thought treats writing as an adventure, as a road without a previously defined goal.